Soft $A$-Metric Spaces - Çiğdem Gündüz; Servet Kütükcü; Hande Poşul (Journal of New Theory)
This paper draws on the theory of soft $A$-metric space using soft points of soft sets and the concept of $A$-metric spaces. This new space has great importance as a new type of generalisation of metric spaces since it includes various known metric spaces. In this paper, we introduce the concept of soft $A$-metric space and examine the relations with known spaces. Then, we examine various basic properties of these spaces: soft Hausdorffness, a soft Cauchy sequence, and soft convergence.